Upgrade of the CMS muon system - Simone Calzaferri (International Journal of Modern Physics A, 2024)
This contribution illustrates the four different detector technologies used in the muon spectrometer of the Compact Muon Solenoid (CMS) experiment, installed on the Large Hadron Collider (LHC), and their future upgrades. These have the aim to cope with the scheduled increase of instantaneous luminosity of the LHC in the so-called High-Luminosity LHC phase. CMS Collab. [J. Instrum. 3, S08004 (2008), https://doi.org/10.1088/1748-0221/3/08/S08004 ].